Analisa Akurasi dari Pendeteksian Berjalan pada Variasi Peletakan Sensor IMU, Filter Kalman dan FIR, serta Klasifikasi KNN dan Naive Bayes - David Isura; Hurriyatul Fitriyah; Rakhmadhany Primananda (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2022)
Development of research in footsteps has been carried out, especially by using IMU sensor. IMU sensor is a system that can detect changes in speed, orientation of the gravitational force. However, the accuracy in measuring